2020
DOI: 10.1111/jfbc.13560
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract ofPaullinia cupanaattenuates renal and hematological effects associated with ketoprofen

Abstract: This study aimed to evaluate the effect of aqueous extract of Paullinia cupana (AEG) against ketoprofen side effects, through biochemical, hematological, and histological parameters. AEG showed antioxidant activity in the DPPH • scavenging (IC 50 = 17.00 ± 1.00 µg/ml) and HPLC analysis revealed that this extract is constituted by antioxidants (caffeine, catechins, theobromine, and polyphenols). In vivo experiments in female Wistar rats demonstrated that alterations in urea, creatinine, and uric acid levels pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
1
1
Order By: Relevance
“…In agreement with previously reported results, guarana showed a high antioxidant activity in vitro [41][42][43][44][45][46]. It is not surprising that the radical scavenging capacity of the extract was so high, given the known hydrogen and electron-donating ability of polyphenols [47].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previously reported results, guarana showed a high antioxidant activity in vitro [41][42][43][44][45][46]. It is not surprising that the radical scavenging capacity of the extract was so high, given the known hydrogen and electron-donating ability of polyphenols [47].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the high procyanidin contents in the herbal matrices, the DPPH assay was selected for the evaluation of the antioxidant activity. The results of all the matrices are reported in [116] were significantly higher in our study compared to the literature data. The comparison with literature data is summarized in Table 7.…”
Section: Antioxidant Activitycontrasting
confidence: 76%
“…Studies demonstrated a half‐maximal effective concentration value (sample concentration providing 50% of antioxidant activity) for seed extracts of Eugenia involucrata (33.6 μg/ml) (Girardelo et al, 2020), aqueous extract of Paullinia cupana (17.0 μg/ml) (Belló et al, 2021), seeds of Euterpe oleracea (8.8 μg/ml) (Barros et al, 2015), and fruit pulp extracts of Caryocar villosum (7.81 μg/ml) (Yamaguchi et al, 2017). Our results showed a significant effect (40% inhibition with 0.1 mg/ml of the P. trifoliata extract), similar to the effect of 0.5 μg/ml of ascorbic acid used as a positive control.…”
Section: Discussionmentioning
confidence: 99%